2012
DOI: 10.1002/jcu.21990
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of sonographic features of invasive ductal mammary carcinoma with age, tumor grade, and hormone‐receptor status

Abstract: Purpose To determine whether presenting sonographic features of invasive ductal carcinomas (IDC) are associated with patient age, tumor histologic grade, and hormonal receptor status. Methods Sonographic features of 101 consecutive cases of IDC seen at ultrasound were retrospectively assessed based on the BI-RADS criteria of posterior acoustic appearance, tumor margins, and echogenicity. Associations between sonographic features and tumor characteristics were statistically evaluated with attention to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 18 publications
5
43
0
Order By: Relevance
“…However, it is now widely known that many tumors may have variable posterior acoustic features; new studies have shown that well-defined margins and posterior enhancement are more likely to represent higher grade tumors and negative receptor status (13,15,16). Our results are consistent with these findings and there is a strong statistically significant correlation between these parameters.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is now widely known that many tumors may have variable posterior acoustic features; new studies have shown that well-defined margins and posterior enhancement are more likely to represent higher grade tumors and negative receptor status (13,15,16). Our results are consistent with these findings and there is a strong statistically significant correlation between these parameters.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, the majority of malignant breast tumors were expected to have posterior acoustic shadowing at US and have poorly defined spiculated margins (13,14). However, it is now widely known that many tumors may have variable posterior acoustic features; new studies have shown that well-defined margins and posterior enhancement are more likely to represent higher grade tumors and negative receptor status (13,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, paradoxically, high-grade tumors were more likely to be well circumscribed. 14,17 High tumor stiffness values for breast malignancy might be particularly useful in high-grade cancers. [40][41][42] In this study, 16 of 98 benign masses were downgraded.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Furthermore, a circumscribed margin on B-mode sonography was associated with a high histologic grade and an aggressive immunohistologic subtype. [14][15][16][17][18] Circumscribed breast cancers might be assigned to an inappropriate lower BI-RADS category on B-mode sonography, 9,19 leading to a delayed diagnosis.…”
mentioning
confidence: 99%
“…In a clinical setting, breast US is highly sensitive, and the National Comprehensive Cancer Network has recommended this modality as the first‐choice imaging examination for mammary disease . As the US imaging characteristics of mammary lymphoma have many similarities to those of breast infiltrating ductal carcinoma (BIDC), misdiagnosis often occurs . However, the treatments of these diseases vary considerably.…”
mentioning
confidence: 99%